Interactive Media as a socialization Agent: Influence of WhatsApp among Adolescents in Nairobi - Ouko Otieno, Denish (2018)
This study focused on interactive media as a socialization agent. The general study objective was to establish influence of WhatsApp mobile application on adolescents, while specific study objectives were; to establish the level of effectiveness of parents/guardians in monitoring adolescents WhatsApp use, assess motivations behind adolescents WhatsApp preference and establish how adolescents access WhatsApp mobile application. Qualitative research approach was used. Data was collected through; semi-structured interviews, participant observation, informal conversations, and focus group discussions. Convenient sampling was used to ease accessibility of target audience. Thematic analysis as qualitative data analysis strategy was used. Data was presented in form of narratives. It was established that parents do not monitor adolescents as they use WhatsApp application, reasons such as parents not being technological savvy, their negative attitude towards learning communication technologies and too much trust on adolescents contributed to lack of monitoring adolescents interactions on WhatsApp. WhatsApp influences were; addiction which resulted in irregular sleeping patterns among adolescents and interference on their studies. Erosion of family values and anti-social behaviour among adolescents were also noted as effect of WhatsApp addiction. The study established that, adolescents’ preferences to use the application were; popularity of WhatsApp hence viewed as trendy and fashionable.